Inhaled Mannitol in the Diagnosis and the Management of Asthma. Issue 6 (November 2016) - Anderson, Sandra D.; Perry, Clare P.; Brannan, John D.
Abstract : The need for a diagnostic test for asthma was established when it was realized that asthma symptoms could not be relied upon to predict the presence, or not, of airway hyper-responsiveness and inflammation, the hallmarks of asthma. A need to identify asthmatic patients who were overtreated or undertreated with inhaled corticosteroids (ICS) has also been recognized. Dry-powder mannitol, given by inhalation, is used as a bronchial provocation test to meet this need. Mannitol is an osmotic agent and causes the release of mediators that provoke the airways to narrow. This airway response to mannitol is dependent on the presence of inflammatory cells, and it is reduced or even completely inhibited by treatment with ICS. Studies in large populations have shown that mannitol has a high specificity (95%) for identifying asthma and can be used to monitor treatment with ICS. Importantly, when mannitol responsiveness is reduced by treatment with ICS, all other indices of airway inflammation are reduced, in association with improvements in clinical symptoms. The responsiveness to mannitol is more frequent than the responsiveness to exercise in both adults and children. Mannitol responsiveness is not necessarily associated with other markers of airway inflammation such as a high exhaled nitric oxide and/or a sputum eosinophilia. This may be due to mast cells being the important cell for the mannitol response. In adults, a negative mannitol test result is common in asthmatic patients taking ICS, and consideration should be given to the back titration of the dose to confirm the diagnosis and reduce risks from overtreatment.